If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + e = 6e + -50 Reorder the terms: 8 + e = -50 + 6e Solving 8 + e = -50 + 6e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-6e' to each side of the equation. 8 + e + -6e = -50 + 6e + -6e Combine like terms: e + -6e = -5e 8 + -5e = -50 + 6e + -6e Combine like terms: 6e + -6e = 0 8 + -5e = -50 + 0 8 + -5e = -50 Add '-8' to each side of the equation. 8 + -8 + -5e = -50 + -8 Combine like terms: 8 + -8 = 0 0 + -5e = -50 + -8 -5e = -50 + -8 Combine like terms: -50 + -8 = -58 -5e = -58 Divide each side by '-5'. e = 11.6 Simplifying e = 11.6
| 19.8=j-34.2 | | 2-5h+15=-28 | | 60-12+36= | | (6-5i)-(3+2i)=0 | | (3m+7)(2m+-1)=0 | | 7+11-3X(2+2)= | | 2+2(x+2(x+2))= | | -9+p=4-p | | 9k+8=32 | | 2-15y=3 | | 7n^2-60n-27= | | 9x^3-36x^2+20=0 | | 5x-4y=2-10x+8y+7 | | 2xy^3+3xy=25 | | p-49.9=2.4 | | 3j+4-j=2j | | -3x+4(3x-1)=41 | | 40x^3-56x^2-45x-63= | | 5y^2-5=0 | | -9(3b+1)+10=53 | | 2x+2y=112 | | M-5m+2m-4= | | 12y+2=21y+13 | | 9x-5+9-5x= | | 18X-4X= | | 38.6=j-28.8 | | 12x+2=4x-1 | | 8+e=1e+5e-50 | | 6y+1=31y+13 | | (x^2)-(4x)+(2)=0 | | 2(x+3)+8=5x-3(-4+x) | | e-11.7=37.1 |